Observational constraints on the origin of the elements: IV. Standard composition of the Sun - Magg, Ekaterina; Bergemann, Maria; Serenelli, Aldo; Bautista, Manuel; Plez, Bertrand; Heiter, Ulrike; Gerber, Jeffrey M.; Ludwig, Hans-Günter; Basu, Sarbani; Ferguson, Jason W.; Gallego, Helena Carvajal; Gamrath, Sébastien; et al. (Astronomy and astrophysics, 2022)
Context. The chemical composition of the Sun is required in the context of various studies in astrophysics, among them in the calculation of standard solar models (SSMs) used to describe the evolution of the Sun from the pre-main-sequence to its present age.Aims. In this work, we provide a critical re-analysis of the solar chemical abundances and corresponding SSMs. Methods. For the photospheric values, we employed new high-quality solar observational data collected with the IAG facility, state-of-the art non-equilibrium modelling, new oscillator strengths, and different atmospheric models, including the MARCS model, along with averages based on Stagger and CO5BOLD 3D radiation-hydrodynamics simulations of stellar convection. We performed new calculations of oscillator strengths for transitions in O I and N I. For O I, which is a critical element with regard to the interior models, calculations were carried out using several independent methods. We investigated our results in comparison with the previous estimates. Results. We find an unprecedented agreement between the new estimates of transition probabilities, thus supporting our revised solar oxygen abundance value. We also provide new estimates of the noble gas Ne abundance. In addition, we discuss the consistency of our photospheric measurements with meteoritic values, taking into account the systematic and correlated errors. Finally, we provide revised chemical abundances, leading to a new value proposed for the solar photospheric present-day metallicity of Z/X = 0.0225, which we then employed in SSM calculations. We find that the puzzling mismatch between the helioseismic constraints on the solar interior structure and the model can be resolved thanks to this new chemical composition.